Non‐alcoholic fatty liver disease phosphoproteomics: A functional piece of the precision puzzle. Issue 13 (19th April 2017) - Wattacheril, Julia; Rose, Kristie L.; Hill, Salisha; Lanciault, Christian; Murray, Clark R.; Washington, Kay; Williams, Brandon; English, Wayne; Spann, Matthew; Clements, Ronald; Abumrad, Naji; Flynn, Charles Robb
Abstract : Background: Molecular signaling events associated with the necroinflammatory changes in nonalcoholic steatohepatitis (NASH) are not well understood. Aims: To understand the molecular basis of NASH, we evaluated reversible phosphorylation events in hepatic tissue derived from Class III obese subjects by phosphoproteomic means with the aim of highlighting key regulatory pathways that distinguish NASH from non‐alcoholic fatty liver disease (also known as simple steatosis; SS). Materials & Methods: Class III obese subjects undergoing bariatric surgery underwent liver biopsy (eight normal patients, eight with simple steatosis, and eight NASH patients). Our strategy was unbiased, comparing global differences in liver protein reversible phosphorylation events across the 24 subjects. Results: Of the 3078 phosphorylation sites assigned (2465 phosphoserine, 445 phosphothreonine, 165 phosphotyrosine), 53 were altered by a factor of 2 among cohorts, and of those, 12 were significantly increased or decreased by ANOVA ( P < 0.05). Discussion: Statistical analyses of canonical signaling pathways identified carbohydrate metabolism and RNA post‐transcriptional modification among the most over‐represented networks. Conclusion: Collectively, these results raise the possibility of abnormalities in carbohydrate metabolism as an important trigger for the development of NASH, in parallel with already established abnormalities in lipid metabolism.